“A penny for your thoughts?”: exploring influences on young accounting professionals' financial behaviour - Govender, Derisa (College of Accounting, 2025)
As new entrants into the workforce and future financial leaders, young professionals are critical to economic success. Therefore, understanding factors shaping their financial behaviour is crucial to improving their personal financial decision-making abilities. Adopting a qualitative approach consisting of semi-structured, open-ended interviews, this study explores the perceived influences on young accounting professionals' personal financial behaviour through the lens of socialisation. Portraying real stories of young South African accountants, active participants in a developing economy, this paper unravels traditional conceptions of determinants of financial behaviour, thus contributing to extant quantitative results. Among South Africa's diverse population of young accounting professionals, households were found to be most influential on all elements of financial behaviour. Increasingly, social media and the Internet influence spending and savings decisions, however the inability to verify online information poses a challenge to how young professionals consume and apply online information in their lives. Thus, these and other findings are instrumental in guiding parents and guardians, educators, and other interested parties in fostering young professionals' financial well-being.